Correlation between the Functional Movement Screen (FMS) Test with Dynamic Balance and Core Endurance in Male and Female Volleyball Players in Kerman Province - Pourheydari, Sara; Sheikhhoseini, Rahman; Hosseini, Seyyed Ghasem (Journal of Clinical Physiotherapy Research, 2018)
Introduction: Functional movement screen (FMS) test may be able to detect athletes who may be at risk of further injury by identification of muscle imbalances and movement impairment syndromes. The aim of this study was to examine the correlation between FMS test and dynamic balance and endurance of core muscles in male and female volleyball players. Materials and Methods: FMS test, the Y balance test and the McGill trunk endurance tests were employed in the present study to evaluate the quality of movement, dynamic balance and the core muscle endurance, respectively. Subjects voluntarily participated in the study for three consecutive days. The correlation coefficient was employed to investigate the relationship between variables. All statistical analyzes were carried out at confidence interval of 95% (P<0.05). Results: 30 volleyball players (men=15, height 183/80±7/82 cm, Weight 74/93±9/58 kg) (Women=15, height 168/93±8/25 cm, Weight 58/13±9/41 kg). The results showed that there is only a significant correlation between the men’s trunk flexor muscles and the left foot balance of the women’s with functional movement test (P<0.05). There was no significant relationship between other measured factors. Conclusion: Considering the results and limitations of the present study, it seems that the correlations between FMS scores and the core endurance and balance may be different between males and females; therefore, further studies are strongly recommended to clarify the issue. Keywords: Athletic Injuries, Lumbosacral Region, Muscle Fatigue, Risk Assessment